TRANSFORMASI EKONOMI KREATIF: KONTRIBUSI FEBI MART DALAM MENUMBUHKAN JIWA ENTREPRENEUR MAHASISWA IAIN KEDIRI - Naning Fatmawatie; Andriani; Widya Ratna Sari; Dewi Fatmala Putri; Faricha Lita Nabbila; Mumtaza Alfahdy; Ikhsan Andi Syahputra (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
FEBI MART functions as a strategic platform designed to encourage students to be active in entrepreneurial activities, as well as being a catalyst for creative economic growth in the campus environment. The focus of this research is how to transform the creative economy: Febi Mart's contribution to fostering the entrepreneurial spirit of IAIN Kediri students. This research was conducted using the focus group discussion (FGD) method and a focused open-ended interview type. The research findings show that FEBI MART contributes significantly to fostering an entrepreneurial spirit among FEBI IAIN Kediri students, through providing a platform for product marketing, assistance with halal certification, and participation in business competitions. This is the right step in supporting the transformation of students' creative economy. However, in reality, there are several challenges that need to be overcome, such as low product creativity and innovation, poor packaging quality, and the use of unofficial halal logos. Increased product oversight, packaging quality training, and encouragement to obtain official halal certification will be critical to ensuring the sustainability and success of this program.